(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2022)
Although post-independent Mauritius has witnessed the evolution of the history curriculum, the discipline has still not been accorded the status as in some countries in Europe and Africa. The evolution also marks change and continuity in the content of the history curriculum and how the teaching is transacted in classrooms. This paper informs on the current state of teaching history in primary schools in Mauritius. An interpretivist qualitative methodological approach was adopted to understand the pedagogical choices made by teachers in the implementation of the history curriculum in primary classrooms. Data was generated through classroom observations and interviews with 15 primary school history teachers. Findings reveal the need to draw on a range of knowledge to engage learners successfully in history classes. This range of knowledge they need to draw is extensive and complex. The study shows that teachers’ knowledge base is crucial for effective history teaching in classrooms.